Pilot wave approach to the NRT nonlinear Schrödinger equation - Pennini, Flavia Catalina (2014)
We investigate the main features of a pilot wave representation of the nonlinear Schrödinger equation recently advanced by Nobre, Rego-Monteiro, and Tsallis (NRT) on the basis of Tsallis q-thermo-statistical formalism. The present approach sheds new light upon the NRT equation. In particular, it suggests a new point of view concerning an apparent inconsistency concerning the physical meaning of its q-plane wave solutions.